(3TaGA GdSGFd Edi JgPjH GdeSGFds - (3YHO GdQMef Hf eMeO Hf eMeO Hf NdOhf, CHh RjO,J (B808 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdEdgGe dMeOg fYeI ef YfOg CeG HYO abO habfi HYV GdENhGf GHbGge Gddg Ydi JaSjQ hUd ef YhQI GdCfOdSi s
(3BNQgG (B:s
(3hbO GfJgi cdGe GdeJfGXQjf hGfJgi HfG fMf GdcdGe dGfJgGFg ced HMeO Gddg hMSf Yhfg s
(3fSNI KGHJIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B330s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs